Hubungan Antara Kebiasaan Merokok dengan Kapasitas Vital Paru - Wijaya Putri, Maulida, Maskun Pudjianto, S.MPh, M.Kes, Isnaini Herawati, S.Fis.,Ftr.,M.Sc (2015)
Background: In the smoker's body changes the structure and function of airways and lung tissue that causes a decrease in lung function. Toxins that accumulate in the lungs can lead to decreased lung capacity. Lung capacity is the greatest amount of air expelled after maximal inspiration. The Objective of Research: To determine the relationship between smoking and lung vital capacity. The Benefit of Research: It could know the relationship between smoking and lung vital capacity. The Method of Research: This type of research in this study was observational with case control study design. The sampling technique is purposive sampling with inclusion and exclusion criteria. Measurement of vital lung capacity using a spirometer, so we get the case group and the control group. Statistical analysis using Chi-Square with a degree of confident by 95%. Result of the Research: Statistical analysis showed smoking may be a risk factor of 5.529 times the decline in lung vital capacity compared with non-smokers. Conclusion: Statistically concluded that smoking may be a risk factor of 5.529 times the decline in lung vital capacity compared to non-smokers.